라섹 수술 후 통증에 대한 비스테로이드성 항염증 점안액의 선행 진통 효과 - 김세경; Se Kyung Kim; 홍진표; Jin Pyo Hong; 남상민; Sang Min Nam; 서경률; Kyoung Yul Seo (Daihan angwa haghoi jabji, 2011)
목적: 라섹 수술 전 점안한 비스테로이드성 항염증점안액의 수술 후 통증 감소에 미치는 선행 진통효과에 대해 알아보고자 한다. 대상과 방법: 라섹 수술을 받은 건강한 성인 31명 62안을 대상으로 수술 30분, 20분, 10분 전에 무작위로 배정한 한쪽 눈에 0.5% Ketorolac 점안액을, 다른 눈에는 위약 Ofloxacin 점안액을 점안하였다. 수술 6, 12, 24, 36, 48, 72시간 후의 통증 정도와 눈부심, 눈물흘림, 이물감 정도를 VAS 척도(0-10점)로 설문조사하였고 결과를 분석하였다. 결과: 수술 6, 12, 24시간 후 평균 통증 점수는 선행진통 점안군에서 각각 2.62, 2.64, 1.1점 낮았으며, 통계적으로 유의한 차이가 있었다(p＜0.05). 수술 36, 48시간 후에는 선행진통 점안군에서 0.54, 0.1점 낮았으나 통계적 유의성은 없었다(p＞0.05). 눈부심은 두 군간에 유의한 차이가 없었으며, 눈물흘림, 이물감은 선행진통 점안군에서 유의하게 낮았다(p＜0.05). 결론: 라섹 수술 전 점안을 통해 선행진통을 시행한 경우, 수술 후 통증 감소 효과가 있었으며, 다른 안과 수술에서도 유용한 통증 조절 방법임을 알 수 있었다. <대한안과학회지 2011;52(12):1414-1418> Purpose: To assess the preemptive analgesic effect of topical NSAIDs (0.5% ketorolac tromethamine, Acular) as postoperative pain relief in patients undergoing LASEK. Methods: A prospective, randomized, placebo-controlled, paired eye study was performed. Patients undergoing LASEK were randomized to receive 0.5% ketorolac in one eye and 0.3% ofloxacin (placebo) in the contralateral eye at 30 minutes, 20 minutes, or ten minutes prior to LASEK. Pain was assessed using a visual analog scale of 0 to 10 in each eye 6, 12, 24, 36, 48 and 72 hours after surgery. Patients were also asked to assess the levels of glare, tearing and irritation using a visual analog scale from 0 to 10. Results: A total of 62 eyes from 31 patients were enrolled in the present study. The mean postoperative pain score in the NSAID group was significantly lower than that in the placebo group at postoperative hours 6 (2.35 versus 4.97), 12 (2.52 versus 5.16), and 24 (3.84 versus 4.94) (p < 0.05). The mean postoperative pain score after 36 and 48hours was also lower in the NSAID group than in the placebo group, but the differences were not statistically significant (p > 0.05). Patients reported significantly less tearing and irritation in the NSAID-administered eye compared to those in the placebo eye after LASEK (p < 0.05). Conclusions: Preemptive administration of topical NSAIDs before LASEK was effective in reducing acute postoperative pain. Preemptive analgesia with topical NSAIDs may be a valuable treatment option for controlling postoperative pain following ocular surgery. J Korean Ophthalmol Soc 2011;52(12):1414-1418